Synopsis of the Japanese species of Aleocharinae (Coleoptera: Staphylinidae), with review of the type specimens II. Genus Myllaena Erichson of tribe Myllaenini,with redescription of four Japanese species - Liu, Tian-Tian; Nozaki, Tsubasa; Yamamoto, Shûhei; Maruyama, Munetoshi (Zootaxa, 2022)
Four Japanese species the rove beetle genus Myllaena are redescribed based on the type material. They are: M. japonica Sharp, 1888, M. lewisi Cameron, 1933, M. rufotestacea Cameron, 1933, and M. torrentum Cameron, 1933. Myllaena chinoculata Pace, 1998 described from China is synonymized with M. lewisi. All of these species are illustrated and mapped.